Charting a Course of Development Through Proper Technical, Technological and Engineering Education - Ajibola, Olawale Olaniyi Emmanuel (Mediterranean Journal of Social Sciences, 2012)
Knowledge refers to the possession of information, facts, ideas, truth or principles. The imparting andacquiring of knowledge through teaching and learning refer to education. The nucleus of education isknowledge. A well directed education is the process that yields knowledge. Engineering is the application ofscience in the design, planning, construction and maintenance of manufactured entity while Engineeringeducation is the training of engineers for the purpose of initiating, facilitating and implementing thetechnological development of a Nation. Engineering uses scientific ideas to develop technology buttechnology provides the ingredient for Engineering. Technical education engenders formal preparation ofTechnicians for occupations between the skilled trades and the professions based on underlying sciencesand supporting mathematics as well as methods, skills, materials, and processes of a specialized field oftechnology. In this work, the roles of these tier of education in the development of a nation was discussedin relation to the existing developmental efforts made towards achieving technological advancement inNigeria. It is hoped that the policy makers in Nigeria will find the paper useful for the betterment of hoipolloi by charting a course of developing the entity called Nigeria through well-found technical,technological and engineering education.